Implementasi Excellent service dalam Meningkatkan Kepuasan Konsumen di Apotek Srikandi Bedahlawak - Damayanti, Sevia (Jurnal Bisnis, Manajemen, dan Ekonomi, 2025)
Assistance Exceptional service is the notion of superior service that prioritizes client happiness by delivering offerings beyond their expectations. This research examines the execution of exemplary service in enhancing customer satisfaction at the Srikandi Bedahalwah pharmacy. The used methodology is descriptive qualitative, with data gathered via interviews and direct observations of service personnel, pharmacists, and patients at the Srikandi Bedahlawak pharmacy. The study's findings suggest that exemplary service includes offerings that surpass client expectations, prioritize quality, use a holistic approach, maintain dynamic service standards, ensure speed and accuracy, exhibit friendliness and accountability, and provide necessary facilities. Moreover, excellent communication between pharmacy personnel and clients and a comprehensive grasp of consumer demands has been shown to enhance the entire customer experience. This research aims to enhance customer happiness at the Srikandi Bedahlawak Pharmacy while also focusing on augmenting client loyalty